Au-Silica nanowire nanohybrid as a hyperthermia agent for photothermal therapy in the near-infrared region - Chen, Jiao (Langmuir : the ACS journal of surfaces and colloids, 2014)
Nanomaterial-based photothermal therapy has shown great potential for efficient cancer treatment. Here, we report a new hyperthermia agent, Au-silica nanowire nanohybrid (Au-SiNW nanohybrid) with tunable optical properties, for photothermal therapy. The unique feature of the synthetic method is no need of surface modification of SiNWs for the direct deposition of Au seeds, which can avoid complicated synthetic procedures and improve the reproducibility. The Au-SiNW nanohybrid can generate significant amount of heat upon irradiation in the near-infrared (NIR) region for inducing thermal cell death. Moreover, compared to reported hyperthermia nanomaterials, the new nanohybrid requires a much lower laser irradiation density of 0.3 W/cm(2) for destroying cancer cells. A549 lung cancer cells were used for in vitro photothermal study. The nanohybrid showed excellent in vitro biocompatibility by using a 96-nonradioactive-cell proliferation assay. Even at a high concentration of 0.500 mg/mL nanohybrid, over 80% cells were alive. In contrast, almost all the cells were killed when NIR irradiation was applied at a concentration of 0.100 mg/mL nanohybrid. The Au-SiNW nanohybrid may become a promising hyperthermia agent